Decoding the domain dynamics of polycrystalline 0.7BiFeO3-0.3BaTiO3 - Xie, Lixu; Khansur, Neamul Hayet; Mo, Mingyue; Gadelmawla, Ahmed; Xing, Jie; Tan, Zhi; Zhu, Jianguo; Webber, Kyle Grant (Journal of Materials Chemistry C, 2024)
Despite the extraordinary significance of high-temperature piezoelectric ceramics in engineered systems, understanding their macroscopic electromechanical response in terms of local underlying phenomena, in particular the domain dynamics at elevated temperatures that directly influence the stability of device performance, remains a significant challenge. Here, we investigate the relationship between domain evolution with temperature and its piezoelectric response utilizing 0.7Bi1.05FeO3-0.3BaTiO3 (BF30BT), a critical alternative to lead-based ferroelectrics for high-temperature applications. By analyzing the frequency and loading amplitude-dependent Rayleigh behavior, we are able to demonstrate the importance of the intrinsic contributions in piezoelectric response. The re-entrant relaxor nature of BF30BT results in active locally heterogeneous nanodomains that display reversible rapid response contributions rather than typical extrinsic contributions due to their low activation energy. Decoding the complicated domain dynamics of BF30BT allows for the further integration of microstructures and macroscopic characteristics, guiding the design and utilization of further high-temperature piezoelectric ceramics.
CRIS-Team Scopus Importer:2024-07-26